Bacterial Dynamics of Hardaliye, a Fermented Grape Beverage, Determined by High-throughput Sequencing - Metin, Banu; Pehlivanoglu, Halime; Yildirim Servi, Esra; Arici, Muhammet (ANKARA UNIV, FAC AGRICULTURE, 2023)
Hardaliye is a traditional beverage produced by fermenting red grapes with mustard seeds and sour cherry leaves in the Thrace region of Turkey. Few studies have been conducted that have determined the microorganisms responsible for hardaliye fermentation, and those that have are limited to lactic acid bacteria (LAB) using culture-dependent techniques. This study aims to determine the bacterial dynamics of hardaliye fermentation using a culture-independent approach, high-throughput sequencing of 16S rRNA amplicons. Hardaliye was produced using the traditional method, and samples were taken and analyzed on days 0, 2, 4, 6, and 10 of fermentation. During the fermentation period, the pH decreased from 3.65 to 3.23. Amplicon sequencing showed that bacterial diversity was highest at 2 d, and lowest at 10 d, the final day. Although Enterobacteriaceae was the most dominant family at 0 and 2 d, Acetobacteriaceae, specifically Gluconobacter frateurii, became dominant with similar to 50% relative abundance at 4 d, and increased its abundance to >98% at 6 and 10 d. Although a slight increase in the relative abundance of similar to 1% (0 d) to similar to 5% (4 d) was observed in LAB, their presence was limited. This study showed that acetic acid bacteria should not be overlooked in hardaliye fermentation.
Keywords: 16S rRNA targeted metagenomics; Acetic acid bacteria; Amplicon sequencing; Fermented foods; Gluconobacter frateurii; ACETIC-ACID BACTERIA; MICROBIAL DIVERSITY; WINE; INSIGHTS; READS; Agriculture